Urotherapy in the treatment of children and adolescents with bladder and bowel dysfunction: a systematic review - Gisela Maria Assis; Camilla Pinheiro Cristaldi da Silva; Gisele Martins (Brazilian Society of Pediatrics, 2019)
Objective: To identify and describe the protocols and clinical outcomes of urotherapy interventions in children and adolescents with bladder bowel dysfunction. Method: Systematic review carried out in June 2018 on Medical Literature Analysis and Retrieval System Online (MEDLINE), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Excerpta Medica dataBASE (EMBASE), Scientific Electronic Library Online (SciELO), Cochrane Library, and PsycInfo databases. Clinical trials and quasi‐experimental studies carried out in the last ten years in children and/or adolescents with bladder and bowel symptoms and application of at least one component of urotherapy were included. Results: Thirteen clinical trials and one quasi‐experimental study were included, with moderate methodological quality. The heterogeneity of the samples and of the methodological design of the articles prevented the performance of a meta‐analysis. The descriptive analysis through simple percentages showed symptom reduction and improvement of uroflowmetry parameters. The identified urotherapy components were: educational guidance, water intake, caffeine reduction, adequate voiding position, pelvic floor training, programmed urination, and constipation control/management. Conclusion: This review indicates positive results in terms of symptom reduction and uroflowmetry parameter improvement with standard urotherapy as the first line of treatment for children and adolescents with bladder bowel dysfunction. It is recommended that future studies bring contributions regarding the frequency, number, and time of urotherapy consultations. Resumo: Objetivo: Identificar e descrever os protocolos e desfechos clínicos das intervenções de uroterapia em crianças e adolescentes com disfunção vesical e intestinal. Método: Revisão sistemática realizada em junho de 2018 nas bases Medical Literature Analysis and Retrieval System Online (MEDLINE), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Excerpta Medica dataBASE (EMBASE), Scientific Electronic Library Online (SciELO), Cochrane Library e PsycInfo. Foram incluídos ensaios clínicos e estudos quase‐experimentais dos últimos 10 anos, em crianças e/ou adolescentes com sintoma urinário e intestinal e aplicação de no mínimo um componente de uroterapia. Resultados: 13 ensaios clínicos e 1 estudo quase‐experimental foram incluídos, sendo a qualidade metodológica moderada. A heterogeneidade da amostra e de delineamento metodológico dos artigos impediu a realização de meta‐análise. A análise descritiva por meio de percentual simples demonstrou redução dos sintomas e melhora dos parâmetros de urofluxometria. Os componentes de uroterapia identificados foram: orientação educacional, ingestão hídrica, redução de cafeína, posicionamento adequado para eliminação, treinamento do assoalho pélvico, micção programada e controle/manejo da constipação. Conclusão: Esta revisão sinaliza resultados positivos em termos de redução de sintomas e melhora nos parâmetros de urofluxometria com aplicação de uroterapia padrão como primeira linha de tratamento nos casos de crianças e adolescentes com disfunção vesical e intestinal. Recomenda‐se que estudos futuros tragam contribuições no que tange a frequência, número e tempo para as consultas de uroterapia. Keywords: Bladder bowel dysfunction, Urotherapy, Behavior therapy, Dysfunctional elimination syndrome, Dysfunctional voiding, Child, Palavras‐chave: Disfunção vesical e intestinal, Uroterapia, Terapia comportamental, Síndrome de eliminação disfuncional, Micção disfuncional, Criança